Forging a New York City Practice Rooted in a Social Agenda - Kimberly Murphy; Claire Webb (Oz, 2013)
Need architects adhere to a social agenda, or any agenda at all? Driven by an ideal of achieving harmony of material and form, architects seek to improve the built environment. How can an architect’s ambitions of reaching “the ideal,” and an impulse to inject theoretical architectural ideas into projects, collide with practical realities of creating progressive educational centers, or housing the homeless and other underserved groups?